Determination of Therapeutic Values of Düzce/Yığılca Honeys by Underlining Overlooked Parameters - Meral Kekeçoğlu; Tuğçe Çaprazlı; Emel Çalışkan; Serpil Uğraş (Turkish Journal of Agriculture: Food Science and Technology)
In this study, we aimed to determine the therapeutic value of local Yığılca honeys by examining their physicochemical characteristics, phenolic content, radical scavenging activity, and antimicrobial properties by underlining some overlooked parameters. Honey samples ware divided into two main groups as CH and FH based on melissopalynologycal analysis. Antimicrobial activity of collected honey samples were investigated on important hospital-acquired infections bacteria strains; MRSA (Methicillin-resistant Staphylococcus aureus), MSSA (Methicillin-sensitive Staphylococcus aureus), Escherichia coli, and Acinetobacter baumannii. Although CH’s antimicrobial activities were found slightly higher than the FH’s, there isn’t statistically significant differences between two type honeys. However, the antioxidant activity of CH was found significantly higher than FH. Surprisingly, a higher amount of isomaltose was determined in addition to the total phenolic content in CH compared to FH. There has been found positive correlation between isomaltose amount and zone diameters for MRSA and A. baumannii. We would like to draw attention to isomaltose for its health benefit structure since these parameters may be influence honey’s therapeutic value. We recommend that isomaltose and invertase enzyme should be included in to the honey codex standards suitably depending on the monofloral and multifloral honey’s specific structure, to sensitively standardize and control their quality and therapeutic value. Our data revealed a positive correlation between antioxidant and antimicrobial activity and total phenolic content and higher isomaltose amount.